DESEMPENHO PRODUTIVO, RENDIMENTO CORPORAL E VIABILIDADE ECONÔMICA DA PRODUÇÃO DO TAMBAQUI (Colossoma macropomum) E HÍBRIDOS TAMBATINGA (Colossoma macropomum x Piaractus brachypomus) E TAMBACU (Colossoma macropomum x Piaractus mesopotamicus) - ANA CARLA CARVALHO SILVA (2022)
The group of aquatic organisms commercially known as “round fish” (genus Colossoma, Piaractus and their hybrids) have shown high growth potential in recent years in Brazil, being second only to tilapia production. This is mainly due to the great acceptability of these fish by consumers, and due to their important zootechnical characteristics, such as omnivorous feeding habits and adequate weight gain, resulting in good production performance in various production systems. Among the most relevant species in this scenario are tambaqui, pacu and pirapitinga. In addition, interspecific hybrids of these species, such as tambatinga e tambacu, are also explored to take advantage of heterosis for weight gain, since the genetic improvement program for tambaqui is still recent and not yet established. Therefore, the objective of this work was to evaluate the productive performance, body yield and economic viability of the production of tambaqui and of the hybrids tambatinga and Tambacu, in net cages, during three production phases. The fish were allocated in nine net cages with 6 m3 of useful volume, divided into three production phases: Phase I (0-77 days of production – 600 fish/net cage); Phase II (77-264 days of production – 200 fish/net cage); and Phase III (264-402 days of production – 100 fish/net cage). In total, 5,400 fishes of the three genetic group were used, which were replicated three times. Production performance variables were evaluated during the experiment, such as, final weight (g), weight gain (g), daily weight gain (g d-1), final biomass (kg and kg m-3), biomass gain (kg), specific growth rate (%), and Fulton condition factor (g cm-3). Morphometric characteristics related to standard length (cm), body height (cm), body width (cm), and head length (cm) were also measured. For the analysis of economic projection, the total operational cost of production of the genetic groups was determined, from the data of the productive performance obtained during the experimental period. In Phase I, no significant difference was observed for production performance between the genetic groups, except for the condition factor and body height which were higher (p < 0.05) in tambatinga, and specific growth rate and body width were higher (p < 0.05) for tambaqui and tambatinga. In Phase II the final weight was higher (p < 0.05) in the groups tambaqui (943.6 g) and tambatinga (686.8 g) in relation to tambacu (276.4 g), the same being true for other characteristics of production performance, being greater (p < 0.05) in tambaqui e tambatinga. In Phase III, a higher (p < 0.05) final weight was observed for tambaqui (1764.1 g) compared to tambacu (654.8 g), whilst the final weight of tambatinga (906.0 g) did not differ from these genetic groups. There were no significant differences in carcass yield percentages between the genetic groups, except for bone yield, which was higher (p < 0.05) in the group tambacu. Among the genetic groups evaluated, the one that showed best economic indicators was tambaqui, which resulted on the decrease of total mean operational cost of production into 47.5% and 33.2% compared to the groups tambacu and tambatinga respectively. It was concluded that in Phase II of production the tambaqui group presented more significant results for morphometric characteristics when compared to the tambatinga group, and for productive performance in relation to the tambacu group; while in Phase III, tambaqui demonstrated higher biomass gain compared to tambatinga, and better productive performance and morphometric characteristics when related to the tambacu group, in addition to having presented body yield similar to the other genetic groups and more attractive economic indicators, with lower total mean operational cost of production.